THE USE OF TERM POSITION DEVICES IN RANKED OUTPUT EXPERIMENTS - MICHAEL KEEN, E. (Journal of documentation, 1991)
Term position information, as provided in some Boolean systems in the form of field restriction and term proximity, is reviewed and its value assessed. Non-Boolean retrieval in the form of the ranked output experiment has not so far used term position information but has concentrated on schemes of term weighting. The use of term proximity devices is proposed here by analogy with Boolean techniques and seven algorithms are devised to incorporate the ideas of sentence matching, proximate terms, term order specification and term distance computations. It is hypothesised that term position will act as a precision device. A new search experiment is then described in which a test collection is processed into sentences and then output ranking using term position is obtained. Results are given for five algorithms compared against quorum searching as the benchmark. The best result increased the precision ratio by 18% and used proximate matching term pairs in sentences plus a distance component.